1988
DOI: 10.1288/00005537-198811000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Type II collagen distribution in rodents

Abstract: The anatomical distribution of type II collagen in animal ears was studied by immunohistochemical techniques, using defined monoclonal antibodies to type II collagen. Type II collagen was observed in the cartilage plate of the auricle and external auditory meatus, tympanic annulus, lamina propria of tympanic membrane (pars tensa), interossicular joints, stapes footplate, eustachian tube cartilage, enchondral layer and globuli interossei of the otic capsule, Rosenthal canal, cribriform base, osseous spiral lami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…3H). These findings are quite coincident with those of the previous reports [30,33]. Moreover, the marginal region with the absence of the type II collagen immunolabeling in the IM joint cartilage matrices was complementally stained with the CS-56 antibody (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3H). These findings are quite coincident with those of the previous reports [30,33]. Moreover, the marginal region with the absence of the type II collagen immunolabeling in the IM joint cartilage matrices was complementally stained with the CS-56 antibody (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The SV joint, on the contrary, where the stapes footplate articulates the vestibular window through the annular ligament is quite different from the other ossicular joints, although both the vestibular surface and the rim of the stapes footplate are also covered with hyaline cartilage. So far, some reports are available on immunohistochemical investigations of the cartilage matrices, such as collagen type II [32,33] and chondroitin sulfate [29] immunostainings. In addition, Ye et al [29] suggested that chondroitin sulfate may play an important role in the development of otosclerotic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune response to the components of connec tive tissue, in particular CII, has long been recognized as important in arthritis, but it was also proposed as impor tant in human ear diseases [9], CII is known as the major component of cartilage but immunohistochemical studies of the ear tissue in rodents have revealed its distribution in the following regions: the enchondral layer and globuli interossei of the otic capsule, osseous spiral lamina, spiral ligament, limbus, tectorial membrane, endolymphatic duct, and other tissue structures [36][37][38][39][40]. Autoimmune response to CII with animal models was originally described as collagen-induced arthritis in rats and mice [21,39], It is known that the onset of arthritis is recognized by redness and swelling of the paws 4-6 weeks after immunization with CII.…”
Section: Discussionmentioning
confidence: 99%
“…This report supports the hypothesis that these two proteins interact with each other. Several types of collagen have been detected in the ECM of the inner ear [Yoo et al, 1988;Slepecky et al, 1992;Usami et al, 2008]. Of these subtypes, type II collagen is responsible for the fibrous structure and appears to play a critical role in maintaining structural stability in the cochlea and vestibule [Slepecky et al, 1992].…”
Section: Discussionmentioning
confidence: 99%